A qualificação da progressão textual em oficinas de produção de texto - Groos, Paola Tassinari (2017)
Teaching in Basic Education, focused on the development of textual production, is fundamental for students to qualify their texts in the school context and also to increase knowledge and textual skills to act in society. Therefore, this dissertation, linked to the Postgraduate Program in Letters, in the area of Linguistic Studies, in the research line Language and Interaction, of the Federal University of Santa Maria (UFSM), proposes to investigate, through methodology of action research, the qualification process of the textual production from Basic Education students, focusing on textual progression. The theoretical framework is based on the notion of language as a form of social interaction, proposed by Bakhtin (1997; 2014); in the socio-interventionist perspective of education, defended by Vygotsky (1984; 1991), in Textual Linguistics, based on Charolles (1978), Beaugrande and Dressler (1983), Koch (2014; 2015) and on the study of textual progression, postulated by Koch (2006) and Koch and Elias (2016). The methodology is anchored in the action research, proposed by Thiollent (1996) and Tripp (2005), that allows the interaction between the research‘s subjects and the researcher. In addition, this methodology offers to the subjects involved subsidies for the transformation of their reality, since it broadens the understanding about characteristics, potentialities or needs existing in the environment. The research was carried out in weekly workshops of textual production, between September and December of 2016, with volunteer students of the High School‘s 2nd year from Santa Maria‘s (RS, Brazil) State School. The corpus analysis is based on Textual Linguistics. As a result, we highlight that, with such research, we found benefits related to the qualification of textual productions, focusing on the development of textual progression, especially, referential progression and thematic progression.